Keterampilan Proses Sains Mahasiswa Biologi Melalui Penerapan Model Pembelajaran Inkuiri Terbimbing pada Praktikum Fisiologi Hewan - Afreni Hamidah (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the effect of the application of the Guided Inquiry learning model on the Science Process Skills (KPS) of Biology Education students at the University of Jambi in 2017/2018 in the Animal Physiology practicum. The method used is true experiment with Post-Test Only Control Design. The research data was obtained by providing a scientific knowledge test in the form of a post-test and an observation sheet for students' science process skills during practicum activities. The results showed that the average value of KPS in the experimental class was 88.24 and the control class was 68.82 with tcount = 36.20. The average scientific knowledge of the experimental class students is 75.35 and the control class is 70.18 with tcount = 7.49. In conclusion, applying the inquiry model to the improvement of KPS and scientific knowledge of Biology Education students at Jambi University in Animal Physiology practicum is an effect. Keywords: Science Process Skills, Guided Inquiry, Scientific Knowledge